(untitled) (Educação e Pesquisa, 2003)
This article reports on the results of the study Infoways and Education carried out from 2000 to 2002 involving four cities of the State of Goiás (Brazil). The purpose of that study was the introduction of the use of technologies in education, particularly information technology, in a pleasurable way, without the stress that usually accompanies experiences of this kind. Among the other objectives of that study were following up the process, identifying and analyzing the needs of those involved with it, as well as, in the long run, producing contents such as texts, didactic materials, video analyses, and support material to teacher education that would be made available through the State of Goiás information network. A qualitative methodology was employed aiming at the intervention in the processes, implementation of activities, following up on them, and analyzing their results. It included offering courses, carrying out theoretical discussions in study groups, organizing academic events, consulting with experts, the production of photo and video materials, and the creation of home pages. The results generated were three undergraduate scientific training reports, a CD-ROM for use in didactics distance learning, and the conception, development and publication of a Virtual Museum of Education. The conclusions led to the understanding that works including technologies in education require the articulation of three dimensions: academic, technical, and managerial, that is, the existence of an institutional policy for the use of technologies in education.